Influence of temperature on the static interface interaction of marine silica sand and geogrid - Feng, Xianhui; Zhang, Jiren; Yao, Xu; Zhao, Haiyang; Jiang, Dunduo; Duan, Wenshuo; Cai, Meifeng (Frontiers in Earth Science, 2025)
Temperature is a key factor influencing the mechanical behavior of the static interface between marine silica sand (SS) and geogrid, which directly impacts the stability and bearing capacity of reinforced soil structures. Despite its importance, there is limited research on the temperature-dependent mechanical properties of the silica sand-geogrid (SG) interface. To address this, a self-designed temperature-controlled large-scale static shear apparatus was used to perform a series of static shear tests on the SG interface, utilizing marine SS particles ranging from 0.075 mm to 2 mm and testing temperatures ranging from −5°C to 80°C. The results revealed a non-linear relationship between shear strength and temperature: as temperature increased from −5°C to 40°C, shear strength decreased, then rose between 40°C and 50°C, before declining again beyond 50°C. The sensitivity of interface shear strength to variations in normal stress remained low at both low and high temperatures. Moreover, the interface friction angle and cohesion showed temperature-dependent fluctuations, initially decreasing, then increasing, and finally declining again. These findings underscore the complex effects of temperature on SG interface mechanics and suggest that temperature must be carefully considered in evaluating the stability and performance of reinforced soil structures under varying environmental conditions.